Burden of Hand Maladies in US Emergency Departments. (March 2018) - Colen, David L.; Fox, Justin P.; Chang, Benjamin; Lin, Ines C.
Background: Hand conditions commonly present to the emergency department (ED), yet data are lacking regarding the magnitude of hand-related conditions in the emergency setting. The purpose of this study is to describe the burden and quantify the health care resource utilization of hand conditions seen in EDs across the United States.Methods: Using the National Emergency Department Sample, we identified all ED encounters by patients at least 18 years of age that were associated with a hand condition in 2009 to 2012. The primary outcomes were prevalence, etiology, and associated health care charges for specific categories of hand conditions.Results: The final sample included 34.4 million ED encounters associated with a common hand condition generating $180.4 billion in health care charges. The volume of hand-related presentations varied in a predictable and cyclical manner, peaking in July and waning in December of each year. Trauma was the most common etiology (77.5%) predominantly due to falls (26.2%) and lacerations (19.7%). Over 4 years, the volume of ED encounters rose (5% increase, P < .001) and as did the resulting health care charges (24.6% increase, P < .001).Conclusions: Our study confirms that hand-related conditions contribute significantly to ED volume and consume a growing quantity of health care resources in the United States. The volume of patients presenting to EDs with hand-related conditions fluctuates cyclically throughout the year. Open wounds are the most common cause of presentation and mostly occur in young adults, followed by joint pain, contusions, and fractures.